Livestock and the environment: finding a balance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Livestock production is now the world's largest land user, and the sector is expanding at an unprecedented rate. The cost to the natural resource base is already too high. As demand for livestock products continues to soar, ways must be found by...